2015
DOI: 10.1002/2015ja021353
|View full text |Cite
|
Sign up to set email alerts
|

Mw dependence of the preseismic ionospheric electron enhancements

Abstract: Ionospheric electron enhancement was reported to have occurred ~40 min before the 2011 Tohoku‐oki (Mw9.0) earthquake, Japan, by observing total electron content (TEC) with Global Navigation Satellite Systems receivers. Their reality has been repeatedly questioned due mainly to the ambiguity in the derivation of the reference TEC curves from which anomalies are defined. Here we propose a numerical approach, based on Akaike's information criterion, to detect positive breaks (sudden increase of TEC rate) in the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
112
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(125 citation statements)
references
References 26 publications
(71 reference statements)
10
112
1
Order By: Relevance
“…In fact, the empirical relationship [ Heki and Enomoto , , Figure 4] suggests that the VTEC rate change for M w ≤ 8 events are less than 2 TECU/h under moderate background VTEC (e.g., 20 TECU) in midlatitudes. Then, the short (<20 min) precursor times cause a problem; i.e., we need a larger moving time window for a robust detection of small trend changes, [see Heki and Enomoto , , Figure 3]. This becomes difficult for earthquakes with short precursor times.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the empirical relationship [ Heki and Enomoto , , Figure 4] suggests that the VTEC rate change for M w ≤ 8 events are less than 2 TECU/h under moderate background VTEC (e.g., 20 TECU) in midlatitudes. Then, the short (<20 min) precursor times cause a problem; i.e., we need a larger moving time window for a robust detection of small trend changes, [see Heki and Enomoto , , Figure 3]. This becomes difficult for earthquakes with short precursor times.…”
Section: Data Processingmentioning
confidence: 99%
“…We set up the start of the excluding window at a certain time between −20 min ( M w 8.0) and −10 min ( M w 7.0) relative to earthquakes. Heki and Enomoto [] showed that onset of the preseismic VTEC anomalies is ~40 min before M w 9 class interplate earthquakes and ~20 min before M w 8 class interplate earthquakes. Here we assume that they start ~10 min before M w 7 earthquakes.…”
Section: Data Processingmentioning
confidence: 99%
“…Apart from these coseismic disturbances, Heki [] found ionospheric electron enhancements starting ~40 min before the 2011 Tohoku‐oki earthquake ( M w 9.0), Japan, using a dense array of continuous GPS stations. Through debates between critical papers [ Kamogawa and Kakinami , ; Utada and Shimizu , ; Masci et al ., ] and replies to them [ Heki and Enomoto , , , ], Heki and Enomoto [] showed that the enhancements preceded eight past earthquakes with M w 8.2 or more. They found that the enhancements started about 20/40 min prior to M w 8/9 earthquakes and that the changes in vertical TEC (VTEC) rates depend on M w as well as background absolute VTEC.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the method Nishimura et al (2013) and Nishimura (2014) used to detect small SSEs in Japan, and to the method Heki and Enomoto (2015) detected trend changes in ionospheric total electron content. The only difference from these past studies is that they looked for discontinuities (Nishimura et al, 2013) or bending (Heki and Enomoto, 2015) while we look for the start of the change expressed with Eq. (1) in this study.…”
Section: Contemporary Seismic Events and Three Hypothesesmentioning
confidence: 99%